Congenital chloride diarrhea misdiagnosed as pseudo-Bartter syndrome - Hossein Saneian; Emad Bahraminia (Journal of Research in Medical Sciences, 2013)
Congenital chloride diarrhea (CCD) is a rare autosomal recessive disease which is characterized by intractable diarrhea of infancy, failure to thrive, high fecal chloride, hypochloremia, hypokalemia, hyponatremia and metabolic alkalosis. In this case report, we present the first female and the second official case of CCD in Iran. A 15-month-old girl referred to our hospital due to failure to thrive and poor feeding. She had normal kidneys, liver and spleen. Treating her with Shohl′s solution, thiazide and zinc sulfate did not result in weight gain. Consequently, pseudo-Bartter syndrome was suspected, she was treated with intravenous (IV) therapy to which she responded dramatically. In addition, hypokalemia resolved quickly. Since this does not usually happen in patients with the pseudo-Bartter syndrome, stool tests were performed. Abnormal level of chloride in stool suggested CCD and she was thus treated with IV fluid replacement, Total parentral nutrition and high dose of oral omeprazole (3 mg/kg/day). She gained 1 kg of weight and is doing fine until present. CCD is a rare hereditary cause of intractable diarrhea of infancy. It should be considered in infants with unknown severe electrolyte disturbances.